The effectiveness of syifa exercise module towards the psychological well-being and quality of life among teachers in Kuala Terengganu - Azmi, Hassan; Abdul Manam, Mohamad; Nor Af'dah, Rameli (2019)
Psychological well-being and quality of life are important aspects of ensuring individual welfare as a whole. Nevertheless, psychological or mental problems often affect humans/people, regardless of their profession and teachers are no exception. Teachers today are frequently wound up either due to the school environment, workload or family stresses. This study aims to utilize/employ the Syifa exercise module to address this problem and improve the teachers’ psychological well-being and quality of life in Kuala Terengganu, as well as to test the effectiveness of the module. This research project is made up of two distinct phases. The first phase of the study focused on the development of the Syifa exercise module specifically its module content, expert evaluation, and pilot study. The second phase then evaluated the module based on the quasi-experimental method. Samples based on inclusive criteria were randomly placed either in the treatment group or controlled group. The treatment/experimental group was exposed to the Syifa exercise whereas, the controlled group performed an exercise regime endorsed by the Ministry of Health Malaysia. Both groups continued the respective exercises for three months. The level of psychological well-being was then tested using the Ryff’s Psychological Well-Being Scale while the quality of life was tested using the World Health Organization's Quality of Life Scale (WHOQOL-BREF). Pre and post-intervention assessments were done to gauge the teachers’ level of psychological well-being and quality of life. The data were analyzed using repeated measures, ANCOVA tests. The findings showed significant differences in the mean between teachers’ psychological well-being and quality of life in the pre and post-intervention assessments for both treatments/experimental and control groups. The means that were recorded post-intervention exhibited a clear-cut difference of teachers’ psychological well-being and quality of life between treatment and control group. Overall, there was a pragmatic rise in mean value within the treatment group in comparison to the controlled group’s psychological welfare and quality of life. The results of this study demonstrated the effectiveness of the implementation of the Syifa exercise module in improving the psychological well-being and quality of life of teachers in Kuala Terengganu. It is expected to be widely used to overcome psychological and mental problems among Malaysia citizens.